Shifting Topographic Activation and 5-HT1A-Receptor Mediated Inhibition of Dorsal Raphe Serotonin Neurons Produced by Nicotine Exposure and Withdrawal - Sperling, Robin (2011)
Nicotine activates serotonin (5-HT) neurons innervating the forebrain and this is thought to reduce anxiety. Nicotine withdrawal has also been associated with an activation of 5-HT neurotransmission, although withdrawal increases anxiety. In each case, 5-HT1A receptors have been implicated in the response. To determine if there are different subgroups of 5-HT cells activated during nicotine administration and withdrawal, we mapped the appearance of Fos, a marker of neuronal activation, in 5-HT cells of the dorsal and median raphe nuclei (DR and MR). To understand the role 5-HT1A receptor feedback inhibitory pathways on 5-HT cell activity during these conditions, we administered a selective 5-HT1A-receptor antagonist and measured novel disinhibited Fos expression within 5-HT cells. Using these approaches, we found evidence that acute nicotine activates 5-HT neurons rostrally and in the lateral wings of the DR while there is 5-HT1A dependent inhibition of cells located ventrally both at rostral and mid levels. Previous chronic nicotine exposure did not modify the pattern of Fos activation produced by acute nicotine, but increased 5-HT1A-dependent inhibition of 5-HT cells in the caudal DR. This pattern was nearly reversed during nicotine withdrawal when there was evidence for caudal activation and mid- and rostral-5-HT1A-dependent inhibition. These results suggest that the distinct behavioral states produced by nicotine exposure and withdrawal correlate with reciprocal rostral-caudal patterns of activation and 5-HT1A-mediated inhibition of DR 5-HT neurons. The complimentary patterns of activation and inhibition suggest that 5-HT1A receptors may help shape distinct topographic patterns of activation within the DR.